PENILAIAN KINERJA KOPERASI BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTRIAN KOPERASI DAN UKM REPUBLIK INDONESIA NOMOR 06/PER/DEP.6/IV/2016 “Studi Kasus pada KPRI Sebra” - Putri, Dewi Melania; Bayangkara, IBK. (Universitas 17 Agustus 1945 Surabaya, 2021)
The purpose of this study is to learn about the performance of the KPRI Sebra in 2018-2020 and its Development Bassed on Regulation of the Deputy for Supervision of the Ministry of Coorperative and UKM of the Republik of Indonesian Number 06/Per/Dep.6/IV/2016. This Research is a qualitative research is the KPRI Sebra and the object of the research are all aspects which include capital, quality of earning asset, management, efficiency, liquidity, independence and growth, cooperative identity and cooperative management in 2018-2020. The results showed that the performance of KPRI Sebra obtained a score of an average of 62,57 and received the tittle of cooperative under supervision, with details: a.) The Capital aspect gets an average score of 11 and is categorized as quite healthy. b.) The quality aspect of earning assets gets an average score of 11,75 and categorized under supervision. c.) Management aspect get an average score of 7,4 and categorized under supervision. d.) Efficiency aspect received an average score of 7 and was categorized under special supervision. e.) The liquidity aspect gets an average score of 3,75 and is categorized as under special supervision. f.) Aspect of independence and growth get the average score is 10 and is categorized as healthy. g.) Aspect of identity get the average score is 7,67 and is categorized as quite healthy. And the development of KPRI’S performance Sebra for three years (2018-2020) in a row obtained a total score of 59,3;63,05;65,55 so it can be said that the performance of KPRI Sebra from 2018-2020 has increased.